2020
DOI: 10.1007/s00330-020-06852-3
|View full text |Cite
|
Sign up to set email alerts
|

A smaller heart-aorta-angle associates with ascending aortic dilatation and increases wall shear stress

Abstract: Objectives The aim of this study was to evaluate whether the orientation of the heart, measured as an angle between the long axis of the heart and ascending aorta midline (heart-aorta-angle, HAA), associates with ascending aortic (AA) dilatation. Furthermore, the association between HAA and wall shear stress (WSS) was studied.Methods HAA was retrospectively measured in 1000 consecutive coronary artery computed tomographic angiography (CCTA) images in patients with low-to-moderate pretest probability for corona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…The association of smaller ascending aorta curvature radius with accelerated aortic growth is consistent with the mathematical model showing that aortic curvature has more impact on the force of blood that is exerted on the aortic wall than other markers associated with accelerated aortic growth such as blood pressure, aortic diameter and patient size [9] . The alteration of blood flow patterns through a sharper curve has also been observed in a study investigating the angle between the heart and the aorta [19] . In that study it was observed that having a smaller heart-aorta angle was associated with increased wall shear stress particularly at the outer curvature of the proximal aorta in patients with ascending aorta dilatation.…”
Section: Discussionmentioning
confidence: 60%
“…The association of smaller ascending aorta curvature radius with accelerated aortic growth is consistent with the mathematical model showing that aortic curvature has more impact on the force of blood that is exerted on the aortic wall than other markers associated with accelerated aortic growth such as blood pressure, aortic diameter and patient size [9] . The alteration of blood flow patterns through a sharper curve has also been observed in a study investigating the angle between the heart and the aorta [19] . In that study it was observed that having a smaller heart-aorta angle was associated with increased wall shear stress particularly at the outer curvature of the proximal aorta in patients with ascending aorta dilatation.…”
Section: Discussionmentioning
confidence: 60%
“…CCTA imaging was performed on the basis of clinical indications; thus, the patients were not exposed to additional radiation and patients' clinical treatment was unaffected by this retrospective study. The population of the present study has also been evaluated in prior publications (14)(15)(16).…”
Section: Methodsmentioning
confidence: 99%
“…Decreasing compliance of the ascending aorta increases the jet speed in the aortic lumen (Figure 2) (56,57). In patients with more prominent angulation between the cardiac outflow tract and the lumen of ascending aorta, the direction of the jet is shifted towards the great curvature of ascending aorta causing higher stress in the affected region (55). It has been reported that angulation increases by age resulting in higher aortic wall stress in the aged population (55,58).…”
Section: Intraluminal Blood Flow Dynamicsmentioning
confidence: 97%
“…However, due to anatomical properties of the cardiac outflow tract and ascending aorta, the jet direction does not comply with the ideality. The intensity and distribution of stress towards the aortic wall caused by intraluminal hemodynamics during systole are related to aortic shape, the angle between outflow tract from the left ventricle to ascending aorta, diameter, and shape of aortic orifice, and aortic wall compliance (51)(52)(53)(54)(55)(56)(57). These factors may alter the speed and direction of the transvalvular blood flow jet from the ideality.…”
Section: Intraluminal Blood Flow Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation